Navigating the Digital Landscape Spatially: Assessing P2P Lending Influence on Banking Performance and Risk in Indonesia - Fitri Susilowati; Suryanto Suryanto (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2025)
Research on the influence of digital finance on banking performance and risk is relevant, given the disparity development of the financial sector in Indonesia. The research method used a quantitative approach with data from the Financial Services Authority (OJK). Data processing employed Arellano Bond's two-step dynamic panel regression analysis (GMM), as the available data range was 2020-2022. The research conclusion asserts that banking performance has decreased due to the influence of Peer-to-Peer (P2P) lending. This research has also established that the influence of P2P presence on banking in Java did not differ from that observed outside of Java. The investigation of the influence of P2P lending on banking risk revealed no discernible effect. When researchers attempted to compare the disparities in the influence of P2P lending on risk, they discovered no differences between Java Island and outside Java Island. It implies that government policies encouraging financial institutions' development with digital platforms do not cause banking performance to decline. As such, stricter regulations on P2P lending are necessary to mitigate the risk of bad credit.